Investigating students’ interest on reading journal articles: Materials, reasons and strategies - Saiful Akmal; Ikhwanna Dhivah; Mulia Mulia (Universitas Syiah Kuala, 2020)
This article investigates students’ reading materials, reasons for reading journal articles, and strategies in handling its difficulties. The data was collected by the use of qualitative method with structured interview. A number of eight students were purposely selected as the participants of this study, each representing eight different units studying in the seventh semester at a university in Banda Aceh, Indonesia. In analyzing the data, this research employed the qualitative descriptive analysis of data organization, data examination and data explanation. The findings showed that the favorite reading materials for students are website articles and social media captions, followed by non-fiction readings and newspapers. It is also found that preparing assignment is the utmost popular reason for reading journal articles for the students. Students also said that looking up in dictionary, internet surfing, consulting friends and lecturers, more practices, predicting the meaning of the words, and partial reading were some strategies they used to tackle the problems of reading journal articles. The implication of this study can be of actual practice to the academic reading course and curriculum and material development, especially for future improvement on students’ reading performance and proficiency.